The Activity of Occupational Health Effort on Five Occupational Health Posts (Pos UKK) in Medan - Syahri, I M; Fitria, M (KnE Life Sciences, 2019)
The act of occupational health effort is performed in Occupational Health Post (Pos UKK) to improve the safety of workers, especially in the informal sector. This study aimed to determine the activities of occupational health efforts undertaken in Pos UKK. This type of research was qualitative, extracting collected information and data through in-depth interviews with the five informant officers of health centers. The results showed that the activities carried out were blood sugar checks, height, and weight, health education about diabetes, clean and healthy behavior, and simple treatment. Activities were related to the identification of hazards in the workplace and health education about the potential and risk of hazards in the workplace, how to work safely and securely, occupational nutrition, accident prevention, and personal protective equipment have not implemented. There were also no recording and reporting of activities related to occupational health efforts in Pos UKK. It was recommended to empower cadres and workplace hazard identification training so that the implementation of occupational health efforts could be more developed. Keywords: Activities of occupational health efforts; Pos UKK; informal sector